Factors Influencing the Susceptibility of Mice to Mycoplasma arthritidis - Cole, B. C. (1973)
Concentrated broth constituents markedly enhanced the development of abscesses after subcutaneous injection of Mycoplasma arthritidis. Under appropriate conditions, both virulent and avirulent strains of M. arthritidis produced toxic effects in mice, as detected by the development of necrotic abscesses and death of the animals. The treatment of mice at birth with M. arthritidis antigens rendered the animals more susceptible to infection with M. arthritidis later in life, as evidenced by increased arthritis after intravenous injection. The injection of M. arthritidis into pregnant mice resulted in a high incidence of abortions. Comparative studies using different mouse strains showed that DBA mice were the most susceptible and BALB/c and C57BL mice were the most resistant to infection by M. arthritidis.